Kombucha Production in Uganda: Quality Aspects and Compliance With Standards - Meeme, Rehema; Mukisa, Ivan Muzira; Mugabi, Robert (Food ScienTech Journal, 2023)
Kombucha is a mildly sweet and acidic fermented tea beverage. Its production and consumption in Uganda have expanded dramatically as a result of its purported nutritional and health benefits. However, there has been little research into the quality and safety of commercially produced Kombucha in Uganda. This study evaluated the quality and safety of certified (n = 27) and uncertified (n = 16) Kombucha on the market. It also assessed the knowledge and practices of Kombucha processors with certified (n = 4) and uncertified (n = 4) products in Uganda. A HACCP plan for Kombucha processing was also developed and validated with one processor. All products passed the Kombucha requirements for Staphylococcus aureus, Escherichia coli, Salmonella spp., and heavy metals (lead, arsenic, mercury, and cadmium). However, 60.47% of the products did not meet the quality and safety specifications for Kombucha failing to meet the acidity (n = 3), alcohol content (n = 14), and yeasts and molds (n = 15). The majority of the processors (n = 6) had very good scores (> 75%) for knowledge and practices related to food safety but did not know the importance of sanitizing equipment. Half of the processors did not know about HACCP, its prerequisites, and the Kombucha specification. Four processors did not use objective methods to test product readiness. Half of the processors did not follow the Kombucha specification and had no HACCP plan. A HACCP plan with three CCPs and five CPs was developed and validated. This study, therefore, informs Kombucha processors and regulators on the safety and quality of Kombucha on the market and the importance of HACCP plan development and implementation in achieving product quality.